2007
DOI: 10.5551/jat.e499
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of Apolipoprotein E and Methylenetetrahydrofolate Reductase in the Japanese Population

Abstract: Aim:The aim of this study is to analyze the effect of apolipoprotein E (apo E) and methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms on serum lipid and homocysteine levels in the general Japanese population. Methods: We analyzed the polymorphisms in individuals randomly selected from among participants of Serum Lipid Survey 2000. Results: The frequency of the 2, 3, and 4 alleles of APOE was 4.2, 85.3, and 10.5%, respectively. Individuals with the genotype 4/ 4 had the highest total and low-density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…The allele frequencies of the APOE polymorphisms (E2 7.11%, E3 79.56%, E4 13.33%) in this study were similar to previous reports among the Thai population (E2 7.18%‐10.42%, E3 77.04%‐77.51%, E4 12.54%‐15.43%) . APOE4 allele in our study was higher than Japanese (10.5%), Han Chinese (7.5%), Taiwanese (7.5%), and Korean (9%) populations but lower than the Malaysian population (20.20%) . These inconsistent results may be due to the specific populations.…”
Section: Discussioncontrasting
confidence: 81%
“…The allele frequencies of the APOE polymorphisms (E2 7.11%, E3 79.56%, E4 13.33%) in this study were similar to previous reports among the Thai population (E2 7.18%‐10.42%, E3 77.04%‐77.51%, E4 12.54%‐15.43%) . APOE4 allele in our study was higher than Japanese (10.5%), Han Chinese (7.5%), Taiwanese (7.5%), and Korean (9%) populations but lower than the Malaysian population (20.20%) . These inconsistent results may be due to the specific populations.…”
Section: Discussioncontrasting
confidence: 81%
“…Therefore, this study did not support the need for testing of remnants if measures of fasting triglycerides are available. This study reported that, unlike the studies above (4,2022), the fasting TG in Honolulu Heart Study group was shown to be an independent predictor of CHD incidence as well as RLP-C. Therefore, Imke el al.…”
Section: Discussionmentioning
confidence: 68%
“…The Framingham Offspring Study and other studies have reported the differences in clinical significance between TG and remnant lipoproteins in the fasting state (4,2022). Namely, fasting remnant lipoproteins are shown to be significantly more predictive of cardiovascular events than fasting TG concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The APOE genotypes and alleles in our study population were similar to those reported in previous studies from Japan and Taiwan. 25,26 Although the e3/e3 genotype and e3 allele are common in both Asian and Caucasian populations, a significant difference in the proportion of e4 alleles has been noted. 17,[25][26][27][28] The e4 allele was found in only 5.7% of our control subjects and has been reported in 5%-10% in other Asian populations, compared with a prevalence of 15%-18% in Caucasians (Table 5).…”
Section: Discussionmentioning
confidence: 98%
“…25,26 Although the e3/e3 genotype and e3 allele are common in both Asian and Caucasian populations, a significant difference in the proportion of e4 alleles has been noted. 17,[25][26][27][28] The e4 allele was found in only 5.7% of our control subjects and has been reported in 5%-10% in other Asian populations, compared with a prevalence of 15%-18% in Caucasians (Table 5). 17,[25][26][27][28] Because the APOE e4 allele is strongly associated with extracranial carotid disease, the lower frequency of the e4 allele in Asians may help explain the low prevalence of this disease in this population.…”
Section: Discussionmentioning
confidence: 98%